Nanobiosensors - Grumezescu, Alexandru Mihai (Nanotechnology in the agri-food industry, 2017)
Nanobiosensors: Nanotechnology in the Agri-Food Industry, Volume 8, provides the latest information on the increasing demand for robust, rapid, inexpensive, and safe alternative technologies that monitor, test, and detect harmful or potentially dangerous foods. Due to their high sensitivity and selectivity, nanobiosensors have attracted attention for their use in monitoring not only biological contaminants in food, but also potential chemical and physical hazards. This book offers a broad overview regarding the current progress made in the field of nanosensors, including cutting-edge technological progress and the impact of these devices on the food industry. Special attention is given to the detection of microbial contaminants and harmful metabolotes, such as toxins and hormones, which have a great impact on both humans and animal health and feed.